Two Uses of Gender in Conversation: A Membership Categorization Analysis - Najib Bouhout (Yayasan Visi Intan Permata, 2019)
Discourse analysts have for a long time focused on the study of gender differences in language. Recent approaches, however, eschew that concern in favor of studying the performative aspects of gender. In line with this, Membership Categorization analysis offers the additional advantage of studying societal members’ gender categorization in conversation, the way it shapes the course of conversation, and its import, and consequences, for the conduct of participants in interaction. Membership Categorization Analysis is used here to spot some practical uses of gender by interactants in mundane talk among friends. More specifically, the article analyses two conversational instances where interactants deploy the categories ‘men’ and ‘manly practices’ to realize particular actions in conversation (suggestion and blame attribution). One finding is that gender categorization does pragmatic actions in interaction. In addition, the article argues that the relevance of gender, as one textual given among many, must be analytically demonstrated empirically in the conduct of interactants rather than invoked for the theoretical concerns of the discourse analyst.